Selection of External Factors for enhanced Technological Acceptance Model for E-Learning - Mohamed Nafrees Abdul Cader (TIERS Information Technology Journal, 2022)
A properly regulated e-learning process is one of the utmost needs of this globe these days due to the pandemic. In that sense, researchers have been conducting research but none of those provide a global solution because of selected external factors and sample size. Therefore, this study provides a significant suggestion to select EFs and future research direction by conducting a systematic review study. Therefore, EFs must include not only student perspectives but also staff and parents, similarly, EFs must include not only user-friendliness, system quality, content quality, satisfaction, and self-efficacy but also technical support, anxiety, privacy, and security. Furthermore, the same study analyzes and suggested the most required future research direction for TAM for E-learning such as Developing VR and augmented reality e-learning tools, understanding the use of e-learning from qualitative perspectives through interview or focus group discussions, and Game-based educational tools. Furthermore, selecting the articles for this study was challengeable due to less number of articles published recently and closed access permission.